Actors and landscape changes in tropical Latin America: challenges for REDD+ design and implementation - Pacheco, P.; Aguilar-Støen, M.; Borner, J.; Etter, A.; Putzel, L.; Vera-Diaz, M.D.C. (Center for International Forestry Research, 2010)
Five dominant trends are occurring in tropical Latin America with implications for land use change: (1) rapid growth of agribusiness, (2) expansion and modernisation of traditional cattle ranching, (3) slow growth of small-scale agriculture, (4) logging in production forest frontiers and (5) resurgence of traditional agro-extractive economies. These trends are driven by global markets and national policies, and have significant impacts on landscape change, with diverse associated trade-offs between agricultural development and forest conservation, and impacts on people’s livelihoods. Agribusiness expansion helps create economic growth but leads to deforestation and tends to concentrate incomes. Cattle ranching demands extensive land surface and creates few jobs, which also leads to forest conversion. Peasant agriculture creates jobs and local income but has diverse impacts on deforestation. Indigenous and community lands help to protect forests, but generate few opportunities for livelihoods improvement. Forest concessions do little damage to forests but concentrate incomes among a few people. These contrasting outcomes call for differentiated policy measures for agricultural development, forest conservation and poverty alleviation. There is a need to manage the expansion of large-scale agribusiness and ranching, whilst improving the economic options of smallholders, indigenous groups and other disadvantaged people. REDD+ schemes may help to reduce pressures on forests by compensating land users for foregone benefits. However, there is a need to balance efficiency in reducing emissions from deforestation and equity in the distribution of economic incentives. No ‘one-size-fits-all’ approach to REDD+ could possibly deliver both cost-effectiveness and equity across such diverse landscapes and groups of actors. Whilst some REDD+ activities should target deforestation hotspots at the forest frontier, national strategies must remain inclusive and ensure that benefits and costs are shared among diverse stakeholder groups according to criteria of political fairness. REDD+ thus must go far beyond the compensation of land users’ opportunity costs in high-pressure areas. It will need to address some of the underlying structural reasons for resource overuse and underdevelopment in tropical forest areas